2006
DOI: 10.1158/1541-7786.mcr-06-0118
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Expression of LKB1 in Breast Cancer Cells Attenuates Angiogenesis, Invasion, and Metastatic Potential

Abstract: LKB1 (also known as STK11) is a recently identified tumor suppressor gene whose mutation can lead to Peutz-Jeghers syndrome, which is characterized by gastrointestinal polyps and cancers of different organ systems. Approximately 30% of sporadic breast cancer samples express low levels of LKB1. This suggests that the LKB1 gene may be related to the tumorigenesis of breast cancer. We reintroduced LKB1 into MDA-MB-435 breast cancer cells that lack the LKB1 gene to investigate how overexpression of LKB1 affects tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
61
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(69 citation statements)
references
References 17 publications
8
61
0
Order By: Relevance
“…Recent findings have also shown evidence that human LKB1 (PAR4) and its target AMPactivated protein kinase control polarity and assembly of tight junction structures in mammalian epithelial cells (13)(14)(15). LKB1 is also defined as a human tumor suppressor protein because germline Lkb1-inactivating mutations characterize Peutz-Jeghers cancer syndrome families, and, furthermore, somatic alterations or reduced gene expression of LKB1 are found in several carcinomas, including carcinomas of breast (16)(17)(18)(19)(20).…”
Section: Silencing Of Lkb1 Enables C-myc To Reinitiate the Cell Cyclementioning
confidence: 99%
“…Recent findings have also shown evidence that human LKB1 (PAR4) and its target AMPactivated protein kinase control polarity and assembly of tight junction structures in mammalian epithelial cells (13)(14)(15). LKB1 is also defined as a human tumor suppressor protein because germline Lkb1-inactivating mutations characterize Peutz-Jeghers cancer syndrome families, and, furthermore, somatic alterations or reduced gene expression of LKB1 are found in several carcinomas, including carcinomas of breast (16)(17)(18)(19)(20).…”
Section: Silencing Of Lkb1 Enables C-myc To Reinitiate the Cell Cyclementioning
confidence: 99%
“…36 Similarly, another study on breast cancer has shown that LKB1 limits cancer cell abilities of metastasis and invasion by downregulating MMP-2 and MMP-9 protein. 37 Our study first found that LKB1 could promote the effect of cisplatin on inhibiting cell migration and invasion. To reveal the related mechanisms, we detected the expression levels of MMP-2 and MMP-9 proteins in different treated groups.…”
Section: Discussionmentioning
confidence: 78%
“…Furthermore, under the stress, energy demand or energy supply imbalance conditions that are typical requirement of the tumor microenvironment leads to increase in the expression of AMPK that alters the cancer cell's flexibility to utilize nutrient glucose directly (Liang and Mills 2013;Herrmann et al 2011). Other studies reported that the knockdown of STK11 in MCF-7 and MDA-MB-435 cells induced migration and invasion of breast cancer cells due to which loss of cell polarity and cell-cell adhesion occurs (Li et al 2014;Zhuang et al 2006).…”
Section: Discussionmentioning
confidence: 99%